Using the Science-Policy Interface Platform of UNCCD to translate current WLE science into policy options to demand driven outputs and accelerate adoption of policy solutions - CGIAR Research Program on Water, Land and Ecosystems (2020)
First draft report on ‘The contribution of integrated land use planning and integrated landscape management to land degradation neutrality’’ developed. It will be submitted. It will be presented at UNCCD COP 15 in 2021